2014
DOI: 10.5750/ejpch.v2i1.695
|View full text |Cite
|
Sign up to set email alerts
|

Can person-free medical knowledge inform person-centered medical practice?

Abstract: We have taken great pleasure in reading the comprehensive and detailed review of the latest development in biomedical clinical practice presented by Miles & Mezzich [1]. We hereby respond to the invitation implicit in the authors’ categorization of their paper as “for discussion”. We feel an urge to add some reflections regarding a core topic not addressed in the paper. But initially, we present our condensed interpretation of Miles & Mezzich’ s text, prior to setting out the ground for our subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Rather, it is a 2-fold form of inadequate knowledge: inadequate knowledge production -resulting from a hesitance to grasp the shortcomings of medicine's traditional perspectives on what constitutes knowledge about the human body; and inadequate knowledge implementation -resulting from a hesitance to apply the wealth of already existing knowledge regarding the interrelatedness of biology and biography [8]. The challenge which the medical profession faces is the need for a kind of knowledge that reflects the fact that human beings are lived bodies, or, as phenomenological philosopher Maurice Merleau-Ponty has put it: a body we have (object) -yet different from all other objects -and a body we are (subject) [14]. The ambiguity inherent in this dual status of the human body is an inevitable feature of the human condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it is a 2-fold form of inadequate knowledge: inadequate knowledge production -resulting from a hesitance to grasp the shortcomings of medicine's traditional perspectives on what constitutes knowledge about the human body; and inadequate knowledge implementation -resulting from a hesitance to apply the wealth of already existing knowledge regarding the interrelatedness of biology and biography [8]. The challenge which the medical profession faces is the need for a kind of knowledge that reflects the fact that human beings are lived bodies, or, as phenomenological philosopher Maurice Merleau-Ponty has put it: a body we have (object) -yet different from all other objects -and a body we are (subject) [14]. The ambiguity inherent in this dual status of the human body is an inevitable feature of the human condition.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, there exists within the field of medicine only a rudimentary tradition for gathering, transferring and emphasizing such personrelated, biographical knowledge, even in the first line of medical care which is served by general practitioners (GPs). The theoretical understanding of the significance of such knowledge has not yet been thoroughly explored [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The US Adverse Childhood Experiences study found a dose-response relationship between adverse childhood circumstances and the number of diseases in adult life, both in the somatic and mental domains [37,38]. Scientific explanations of how adversity gets "under the skin" have been developing and converging over the last decade [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…“Patient preferences and values” are also emphasized in models of evidence-based practice (“The EBM flower”) (Haynes, Devereaux, & Guyatt, 2002). However, the fundamental clinical validity of the hegemonic epistemology of biomedicine as such (the basis for EBM) has rarely been challenged (Kirkengen et al, 2013). Consequently, the discourse on “patient preferences and values,” and the associated training in patient-centered communications, typically aims at eliciting patients’ views and preferences with reference to biomedically defined problems and options.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the emphasis has begun to shift from the patient to the person , as reflected in the new terms “person-centered” (Miles & Mezzich, 2011) and “person-focused” medicine (Starfield, 2011). It has been postulated that this emerging interest in the needs of the particular individual, as opposed to an “average” patient, has come in reaction to an on-going dehumanization of medicine as an increasingly predominating focus on standardized technological cure may be in danger of taking precedence over attention to individualized human care (Kirkengen, Mjølstad, Getz, Ulvestad, & Hetlevik, 2013; Miles & Mezzich, 2011). …”
mentioning
confidence: 99%